2015
DOI: 10.15436/2377-1372.15.015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Simulated Workplace Protection Factors Offered by N95 and P100 Filtering Facepiece and Elastomeric Half-Mask Respirators against Particles of 10 to 400 nm

Abstract: This study compared the simulated workplace protection factors (SWPFs) between NIOSH-approved N95 respirators and P100 respirators, including two models of filtering facepiece respirator (FFR) and two models of elastomeric half-mask respirator (EHR), against sodium chloride particles (NaCl) in a range of 10 to 400 nm.Twenty-five human test subjects performed modified OSHA fit test exercises in a controlled laboratory environment with the N95 respirators (two FFR models and two EHR models) and the P100 respirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(34 reference statements)
0
4
0
Order By: Relevance
“… - Product. Costs -Fit test costs - Continuous use of N95s - Fit testing vs no fit testing - Costs and factors may not be similar across countries [ 30 ] - UV disinfection system - UV penetration - Disinfection - Layer disinfection does not reflect reality [ 3 ] - Filtration efficiency testing - Filtration protection - Patient care interference - Testing with low pressure drop for breathing - Testing was limited to two bacteria [ 41 ] - Randomized simulated workplace study - Fit test - Effect on attention - Muffled speech - Difficulty hearing - Dizziness - Fatigue -Breathing -Skin irritation - Other costs and market considerations impact respirator adoptability [ 17 ] - Quantitative fit test - Ambient air particle concentration measurements - Face seal leakage and fit testing -Workload induced heavy breathing - Need for frontline workers investigation [ 9 ] - Simulated workplace protection factor testing - Facial measurements - Sex-stratified analysis - Face seal leakage and fit testing - Only considers respirator and facial dimensions as design factors …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… - Product. Costs -Fit test costs - Continuous use of N95s - Fit testing vs no fit testing - Costs and factors may not be similar across countries [ 30 ] - UV disinfection system - UV penetration - Disinfection - Layer disinfection does not reflect reality [ 3 ] - Filtration efficiency testing - Filtration protection - Patient care interference - Testing with low pressure drop for breathing - Testing was limited to two bacteria [ 41 ] - Randomized simulated workplace study - Fit test - Effect on attention - Muffled speech - Difficulty hearing - Dizziness - Fatigue -Breathing -Skin irritation - Other costs and market considerations impact respirator adoptability [ 17 ] - Quantitative fit test - Ambient air particle concentration measurements - Face seal leakage and fit testing -Workload induced heavy breathing - Need for frontline workers investigation [ 9 ] - Simulated workplace protection factor testing - Facial measurements - Sex-stratified analysis - Face seal leakage and fit testing - Only considers respirator and facial dimensions as design factors …”
Section: Discussionmentioning
confidence: 99%
“…In this regard, EFRs have an advantage due to more adjustable components as highlighted by Zhuang et al. [ 9 ]. Perhaps, APFs should be based not only on the type of mask and mask size, but typical duration of use before leakage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Later studies (Sietsema et al 2015, Sietsema andBrosseau (2018) showed a good correlation between FFs and the SWPF result (measuring face seal leakage only) when the respirator was not doffed in between. He et al (2015) measured the SWPF performance of N95 and P100 filtering facepiece and elastomeric halfmask respirators when challenged with an aerosol in two particle size ranges, with no difference found. Or et al (2016) and Wu (2018) measured real-time face seal leakage for different models of N95 respirators using optical particle counting-based instruments, with Or et al finding an instantaneous PF of less than 10 more frequently in nurses performing moving exercises with heavy activity, in clinical settings.…”
Section: Introductionmentioning
confidence: 99%